CONSEQUENCES OF CASH CONVERSION CYCLE ON FIRM’S PROFITABILITY: REAL ESTATE RELATED SECTORS IN PAKISTAN - Ahmad, Muneeb Ahmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Working capital organization has its effect on liquidity too on productivity of the firm. In this investigation, we have picked a case of 20 Pakistani firms recorded on Karachi Stock Exchange for a period of 10 years from 2010-2019, we have inspected the effect of different elements of working capital organization including the Typical combination time span, Stock turnover in days, ordinary portion period, and Cash change cycle on the net working advantage of Pakistani firms. Current Extent, impact, size of the firm (assessed similar to basic logarithm of arrangements) and improvement have been used as control factors. Backslide examination (Pooled least square) are used for assessment. The results show that there is a strong negative association between elements of the working capital organization and efficiency of the firm. It infers that as the cash change cycle extends it will provoke reducing advantage of the firm, and bosses can make a positive motivating force for the speculators by diminishing the cash change cycle to a possible least level. We moreover find that there is a negative association between size of the firm and its efficiency. There is also an essential negative association between commitment used by the firm and its benefit.